Impact of Post-Thaw Incubation Time of Frozen Embryos on Clinical Pregnancy Rate - G. Geovin Ranji; Kundavi Shankar; Yamini Asokan; Geetha Veerasigamani; Rashmi Gingade Vittal; Nithya M. Naaram; KR Hema Niveda (Journal of Human Reproductive Sciences, 2023)
Background: Vitrification of embryos following a single-controlled ovarian stimulation has been the strategy practised now in many in vitro fertilisation clinics to minimise the risk of early ovarian hyper stimulation syndrome, to reduce multiple pregnancy rates and to improve cumulative pregnancy rates. In recent years, advances in vitrification techniques and improved culture conditions have led to good post-thaw embryo survival rates, thereby increasing pregnancy rates of frozen embryo transfer (FET) cycles. Aim: The aim of this study was to analyse the effect of post-thaw incubation time of frozen embryos on the clinical pregnancy rates (CPRs) of frozen embryo transfer (FET) cycles. Settings and Design: This was a retrospective, comparative study done at a teaching hospital in assisted reproductive treatment. Materials and Methods: Three hundred and ten FET cycles were analysed, of which 125 had day 2 freezing and 185 had day 3 freezing. Depending upon the day of thawing and day of transfer, FET cycles were divided into six groups: Group 1 (day 2 thawing and day 3 transfer), Group 2 (day 2 thawing and day 4 transfer), Group 3 (day 2 thawing and day 5 transfer), Group 4 (day 3 thawing and day 3 transfer), Group 5 (day 3 thawing and day 4 transfer) and Group 6 (day 3 thawing and day 5 transfer). Statistical Analysis Used: Statistical analysis was performed using version 14 R software version 4.0.1 (2020-06-06) (R foundation for Statistical Computing, Vienna, Austria). A P < 0.05 is taken as significant. Results: The CPR of Group 4 was 42.4% which was more than that of the other groups but it did not reach statistical significance. Conclusions: Short incubation time of 2–4 h is as effective as an extended incubation time in terms of CPRs of FET cycles.